A primary interface selection policy in heterogeneous networks based on QoS - Masud, M. H.; Anwar, Farhat; Bari, S.M. Sadakatul (2012)
The number of wireless applications, services and devices such as mobile telephone handsets, laptops and personal digital assistant (PDAs) are growing rapidly. The next generation wireless technology systems are being devised with the vision of heterogeneity where a mobile user will be connected with multiple wireless networks like GPRS/UMTS, IEEE 802.1x, WiMAX and satellite etc. To connect the above devices, a primary interface can be assigned to a mobile node (MN). Mobile users should be connected with appropriate interfaces based on the application types and its requirements. Different types of services are provided by the Internet like file transfer, telephony, audio and video conferencing etc. Among these applications some are sensitive to delay, for example, audio and video conferencing and some are sensitive to quality like file sharing and remote login. This paper proposes a policy that determines different applications’ requirements and chooses an appropriate interface as a primary interface for respective application based on the networks condition to improve Quality-of-Service (QoS). Prior to forward a packet to the destination, the routers decide the routes for that data packet to an appropriate interface that have been selected by the routers. It also helps to select the primary address among all available addresses based on an algorithm and reduces network overloads.